A Very Strong Methylation Agent: [Me2Cl][Al(OTeF5)4]. Issue 29 (17th June 2019) - Hämmerling, Sebastian; Thiele, Günther; Steinhauer, Simon; Beckers, Helmut; Müller, Carsten; Riedel, Sebastian
Abstract: A new chloronium‐containing salt, [Me2 Cl][Al(OTeF5 )4 ], was synthesized on multigram scale by means of a simple one‐pot procedure. The isolated product can be handled at room temperature and used as a strong electrophilic methylation agent. This is demonstrated by the methylation of the very weak bases P(CF3 )3, PF3, MeI, and MeBr. Abstract : A chloronium‐containing salt, [Me2 Cl][Al(OTeF5 )4 ], was synthesized on multigram scale by means of a simple one‐pot procedure. The isolated product can be handled at room temperature and used as a strong electrophilic methylation agent. This is demonstrated by the methylation of the very weak bases P(CF3 )3, PF3, MeI, and MeBr.